Exploring the Dynamic that Influence Students’ Insight in the EFL Speaking - Nelson, Deepika (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2017)
Learners all over the world find complexity in learning English. Several, rationales that hinder their learning process. Motivation is one of the insights that influence the students in the speaking classroom. Dornyei, (2005) stated ‘’ without sufficient motivation, even individuals with the most remarkable abilities cannot accomplish long term goals, and neither appropriate curricula and good teaching is enough to ensure students achievement. In order to obtain a deeper insight into students reflection on their motivational process, Madrid and Canado( 2001) defined a concept of motivation as one’s internal state which is influenced by certain need or beliefs which engender constructive attitudes and interest towards a goal. These attitudes later create constant endeavor on entity because of the satisfaction experienced along with the positive results that have been obtained. This study is going to explored the dynamics that influence students insight in the EFL speaking classroom. A Mixed method approach which included both qualitative and quantitative method was used. A systematic random sampling technique was employed